STUDIES ON GLYCOGEN NEPHROSIS IN ALLOXAN-TREATED DIABETIC RATS - Curtis, G. W. (The Rockefeller University Press, 1947)
Two hundred and seven albino rats were injected subcutaneously with alloxan in doses varying from 140 to 200 mg. per cent per kilo of body weight. Fifty-nine animals which developed hyperglycemia (blood sugar levels above 150 mg. per cent) were observed for periods from 5 days to 32 weeks. Postmortem examination of the kidneys of these diabetic animals revealed glycogen deposition in the loops of Henle and convoluted tubules in 26 rats or 44 per cent. Glycogen could not be demonstrated in the glomeruli. Within the time limits of this experiment (32 weeks) no intercapillary glomerulosclerosis was observed. The following facts were revealed regarding glycogen nephrosis in alloxan diabetes: (a) Its appearance in the kidneys of the diabetic rats depended solely upon the terminal blood sugar levels of these animals. A value of 350 mg. per cent was the critical level, above which glycogen nephrosis was almost invariably demonstrable. With terminal levels below 300 mg. per cent no glycogen nephrosis was found. (b) No relationship existed between the postmortem finding of glycogen nephrosis and the initial blood sugar level, or the maximum height of the hyperglycemia attained by individual rats. (c) The results suggest that glycogen nephrosis is a reversible lesion.